Etude des systèmes à base de phosphates, d’oxydes spinelles, de ferrites et d’hexaferrites pour le stockage d’énergie dans les batteries Li-ion et les nanomatériaux magnétiques : Modélisation par la DFT. - Chouaib AHMANI FERDI (Faculté des Sciences de Rabat, 2021)
The present thesis presents a modeling study of systems of phosphates, spinel oxides, ferrites and hexaferrites using first-principles calculations within the density functional theory. The projector augmented wave (PAW) method was used for the geometrical optimization of the studied systems, while the all-electron linearized augmented plane wave (FP-LAPW) method was used for the calculation of the total energies as well as the magnetic, electrochemical and electronic properties of the studied systems. The combination of these two methods has led to results in very good agreement with the experimental results from our research team and/or from the literature.
Study of systems based on phosphates, spinel oxides, ferrites and hexaferrites for energy storage in Li-ion batteries and for magnetic nanomaterials: DFT modelling.
Keywords: Physique; Physique